Celastrol enhances Atoh1 expression in inner ear stem cells and promotes their differentiation into functional auditory neuronal-like cells. (3rd April 2018) - Han, Zhao; Gu, Yu-yan; Cong, Ning; Ma, Rui; Chi, Fang-lu
ABSTRACT: We aimed to investigate the beneficial effect of Celastrol on inner ear stem cells and potential therapeutic value for hearing loss. The inner ear stem cells were isolated and characterized from utricular sensory epithelium of adult mice. The stemness was evaluated by sphere formation assay. The relative expressions of Atoh1, MAP-2 and Myosin VI were measured by RT-PCR and immunoblotting. The up-regulation of MAP-2 was also analysed with immunofluorescence. The in vitro neuronal excitability was interrogated by calcium oscillation. The electrophysiological property was determined by inward current recorded on patch clamp. Our results demonstrated that Celastrol treatment significantly improved the viability and proliferation of mouse inner ear stem cells, and facilitated sphere formation. Moreover, Celastrol stimulated differentiation of mouse inner ear stem cells to neuronal-like cells and enhanced neural excitability. Celastrol also enhanced neuronal-like cell identity in the inner ear stem cell derived neurons, as well as their electrophysiological function. Most notably, these effects were apparently associated with the upregulation of Atoh1 in response to Celastrol treatment. Celastrol showed beneficial effect on inner ear stem cells and held therapeutic promise against hearing loss.